Robert Bruce : and the community of the realm of Scotland - Barrow, G. W. S. (University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1965.
Description based upon print version of record.
Keywords: Robert -- I, -- King of Scots, -- 1274-1329.; Robert -- I, -- King of Scots, -- 1274-1329; Scotland -- History -- War of Independence, 1285-1371.; Écosse -- Histoire -- 1285-1371 (Guerre d'indépendance); HISTORY / Europe / Great Britain / Scotland; Scotland; 1285-1371; History